Breaking Old Boundaries: Strengthening the Competence of Al-Qur'an Hadith Teachers in the Era of Merdeka Curriculum - Hasibuan, Putri Anggita Sari; Darlis, Ahmad (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This qualitative study aims to examine the strengthening of pedagogical competence among Al-Qur’an Hadith teachers in implementing the Merdeka Curriculum at MAN 2 Model Medan. The research focuses on the efforts made by teachers, the strategies adopted by the school, and the challenges encountered during the process of competence development. The study involved Al-Qur’an Hadith teachers, the vice principal for curriculum affairs, and students as supporting informants. Data were collected through in-depth interviews, participatory observations, and document analysis. The data analysis followed a systematic procedure, including data reduction, data display, and conclusion drawing. The findings indicate that the pedagogical competence of Al-Qur’an Hadith teachers at MAN 2 Model Medan is generally good but has not yet reached an optimal level, particularly in relation to the demands of the Merdeka Curriculum, which emphasizes differentiated, student-centered learning. Efforts to enhance pedagogical competence include participating in seminars and training programs, being actively involved in subject teacher forums (MGMP), listening to scholarly lectures, and increasing literacy through relevant reading materials. Simultaneously, the school administration plays a strategic role by organizing technical guidance and training sessions, conducting internal workshops, fostering collaboration with external stakeholders, and implementing regular academic supervision. These findings highlight the importance of synergy between individual teacher initiatives and institutional support in enhancing pedagogical quality to effectively meet the challenges of Merdeka Curriculum implementation in Islamic schools.